Determination of the antioxidant activity of kaempferia galanga (cekur) in an fe-induced lipid peroxidation system / Muhamad Faiz Othman - Othman, Muhamad Faiz (2006)
Antioxidants play a major role in terminating the lipid peroxidation process and in scavenging free radicals. Phenolic compounds, which can be easily found in the plant kingdom, have been proven by many researchers to be potent antioxidants. A popular Malay herb, Kaempferia gal.anga or locally known as cekur, was reported to contain quite a lot of phenolic compounds. This study thus was carried out with the aim of determining the antioxidant activity of Kaempferia galanga using the Fe2+/NADPH induced lipid peroxidation microsomal system. The ethyl acetate extract of Kaempferia gal.anga was prepared prior to this study by a Msc. candidate. For the induction of lipid peroxidation in microsomes, iron was utilized as the free radical generator in the presence of NADPH. In this study, the optimum concentration of iron for induction of lipid peroxidation was determined. The results showed that the optimal iron concentration to initiate lipid peroxidation was 15 µM. The antioxidant activity of Kaempferia galanga ethyl acetate extract was measured using this established Fe2+/NADPH system. Lipid peroxidation was monitored by the thiobarbituric acid reactive substance (fBARS) method. Trolox and quercetin were use as positive control as both compounds are potent antioxidant. The results showed that Kaempferia gal.anga ethyl acetate extract possess antioxidant activity although not as potent as the controls (trolox and quercetin). The concentration which inhibits lipid peroxidation by 50% (inhibiting concentration; IC50) for the rhizome extract of Kaempferia galanga was 0.03 mg/ml while for leaf extract, it was 0.014 mg/ml.The ICso for trolox was 0.003 mg/ml The IC50 for quercetin could not be determined as it has very potent antioxidant activity even at very low concentrations in this system. In summary, the results obtained showed that the ethyl acetate extract of Kaempferia galanga (both rhizome and leaf) possessed antioxidant in vitro activity as both produced inhibition of lipid peroxidation although their magnitude of activity as not high as trolox and quercetin. Potency was half that of trolox for the leaf extract and a magnitude lower for the rhizome extract based upon a comparison of the IC50 values.